Kromi çan bllokadën – Albanian chromium mining revisited - Göler, Daniel; Bickert, Matthias; Doka, Dhimiter (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Chromium mining was one of the main economic pillars of socialist Albania. In the 1990s, in the wake of the economic transition, extraction nearly stopped altogether. However, chromium mining has undergone a certain revival since the beginning of the 21st century. Its background, context, problems and perspectives are highly diverse. In the following paper, these aspects will be assessed in a differentiated analysis and an evaluation from the position of a critical resource geography. On the one hand, chromite ore is exceedingly rare and highly valuable, which determines both global demand and economic dependencies. On the other hand, inefficiency, low levels of professionalism and widespread informality hinder a renewed economic valorisation of chromium as a resource. The study follows the commodity chain of chromium. Besides macro- and microeconomic issues, a variety of social and geographical aspects as well as the influence of variables relating to resource governance are discussed, both based primarily on qualitative field research. In addition, issues relating to competitiveness and perspectives on settlement and regional development are critically examined.